Efficient Financial Allocation and Productivity Growth in Brazil - Calice, Pietro (World Bank, Washington, DC, 2018)
This paper attempts to study the impact of Brazilian Development Bank credit on resource misallocation in Brazil, using manufacturing firm-level data from 2003-14. The paper first estimates measures of resource misallocation based on Hsieh and Klenow (2009), documenting high variation in firms' capital and output distortions. It then estimates the effect of financial frictions and access to Brazilian Development Bank loans on distortions and their dispersions. The analysis finds some preliminary evidence that the use of Brazilian Development Bank credit is not associated with a more efficient allocation of resources. The lower cost of Brazilian Development Bank loans reduces the marginal cost of capital, as it induces firms to reallocate inputs from labor to capital, and this effect is amplified for more financially dependent firms. The findings, together with extant evidence on the economic additionality of the Brazilian Development Bank, suggest that there is room for improving the allocative efficiency of the earmarked credit system in Brazil.